CMV and HSV Pneumonia After Immunosuppressive Agents for Treatment of Cytokine Release Syndrome Due to Chimeric Antigen Receptor–modified T (CAR-T)-Cell Immunotherapy. Issue 9 (9th November 2021) - Heldman, Madeleine R.; Ma, Jimmy; Gauthier, Jordan; O'Hara, Riley A.; Cowan, Andrew J.; Yoke, Leah M.; So, Lisa; Gulleen, Elizabeth; Duke, Elizabeth R.; Liu, Catherine; Turtle, Cameron J.; Hill, Joshua A.
Abstract : Pneumonia due to cytomegalovirus and herpes simplex virus-1 caused substantial morbidity after hematopoietic cell transplantation before the institution of preventative approaches. End-organ disease from herpesviruses is poorly described after chimeric antigen receptor–modified T-cell immunotherapy. We report 2 cases of cytomegalovirus pneumonia and 1 case of herpes simplex virus-1 gingivostomatitis, esophagitis, and pneumonia after chimeric antigen receptor–modified T-cell immunotherapy for the treatment of hematologic malignancies.